'Che credeva, che fossi Cenerentola!': Changes of Clothes, Guest Appearances, and Other Diva Performances in 1950s Cinema. (August 2015) - Noto, Paolo
<x content-type="archive" xml:space="preserve">Abstract</x> Italian female stars of the 1950s are often subject to the gaze of male characters as they dress or undress. In this article, I analyse this cliché and others, such as dances, partial stripteases, and guest appearances, as textual topoi, in order to define how visual attractions attained a narrative function consistent with the fragmentary character of that cinema. The frequent visual linking of feminine beauty and consumer goods also helps to re-frame, historiographically, the issue of stardom in the early 1950s, and to identify that period as a complex one in which the female body was no longer visualized as an element able to link the cinematic representation to a supposed state of nature, but not yet displayed as a completely commodified object.